An Analysis of the arithmetic test in the U.P. High School entrance examination - Yap, Paz (Yu) 1929- (s.n.], 1966)
This study presents some information on the content and predictive validity, reliability, and item analysis of the arithmetic test in the UP High School entrance examination in the year 1965. As a consequence of this study, the researcher suggested a revised version of the test.